2017
DOI: 10.5114/biolsport.2017.69824
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of swimming on bone in adolescents: a pQCT and DXA study

Abstract: The aims of the present study were, firstly, to evaluate areal bone mineral density (aBMD), bone strength and structure during a swimming season and compare them to those of normo-active controls (CG), and secondly to ascertain whether practising an additional weight-bearing sport other than swimming might improve bone. Twenty-three swimmers who only swam (SWI-PURE; 14 males, 9 females), 11 swimmers who combined swimming with an additional weight-bearing sport (SWI-SPORT; 8 males, 3 females) and 28 controls (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Longitudinal studies also suggest that long-term participation in high-intensity bone-loading sports leads to beneficial skeletal adaptation that is sustained into adulthood. A study in collegiate male and female swimmers showed greater increases in areal BMD (aBMD) at the hip and several tibia parameters in those who performed an additional weight-bearing sport versus those who only swam and non-athlete controls [47]. Faulkner et al showed that total body, lumbar spine, and hip aBMD were significantly greater for elite prepubertal female gymnasts versus age-matched controls [48], and a follow-up study showed that differences were maintained even when gymnasts had been retired for ten years on average [49].…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Longitudinal studies also suggest that long-term participation in high-intensity bone-loading sports leads to beneficial skeletal adaptation that is sustained into adulthood. A study in collegiate male and female swimmers showed greater increases in areal BMD (aBMD) at the hip and several tibia parameters in those who performed an additional weight-bearing sport versus those who only swam and non-athlete controls [47]. Faulkner et al showed that total body, lumbar spine, and hip aBMD were significantly greater for elite prepubertal female gymnasts versus age-matched controls [48], and a follow-up study showed that differences were maintained even when gymnasts had been retired for ten years on average [49].…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Previous studies have sought to understand the isolated effect of different protocols of RT on bone health of adolescents showing its beneficial effect on aBMD accrual [ 19 , 20 ]. While other studies available in the literature have analyzed the joint effects of sports, such as swimming, when added to impact sports [ 21 ] or different interventions as plyometrics [ 22 ] and whole-body vibration on bone health [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even through a short eightmonth period, it was apparent through DXA and pQCT assessment that swimmers who participated in weight-bearing sports concurrently with swimming were likely to have better bone health than those that participated in swimming alone. This suggests that complementing swimming with weight-bearing sports activity may be beneficial to bone health status (Gomez-Bruton et al, 2017;Miller et al, 2020).…”
Section: Long-term Recreational Sports Participation and Bone Healthmentioning
confidence: 99%